(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Violence in relationships is a concern that transcends geographical borders and markers of time. For the purpose of this report, violence in relationships refers to any form of physical, sexual, emotional, and financial abuse or violence perpetuated against females within a relationship. Furthermore, they may also be sexually assaulted by their intimate partners and the violence often increases in frequency andor severity after they separate from their partner – in comparison, male victims did not experience such forms of victimization. Violence in relationships not only results in physical harm, but it “also undermines the social, economic, psychological, spiritual and emotional well-being of the victim, the perpetrator and the society as a whole”. Viciousness against women submitted by their cozy accomplices can be broke down through the Ecological Model, which clarifies the nearby connection among people and their condition. Elements impacting individuals’ conduct towards this viciousness ought to be broke down with a view to setting up help programs. One hypothetical base to comprehend viciousness against women is the Ecological Model. This proposition depends on various creators’ work and proposes a coordinated environmental system with a view to considering and becoming acquainted with Violence against women.